Imaging pair-correlated reaction cross sections in F + CH3D(νb = 0, 1) → CH2D(ν4 = 1) + HF(ν). Issue 26 (10th July 2018) - Yang, Chung-Hsin; Hu, Li-Li; Liu, Kopin
Abstract : Product pair-correlated distributions in the title reactions are revealed by imaging the state-tagged CH2 D( ν 4 = 1) products. Abstract : The title reactions were studied in a crossed-beam experiment at collisional energies ( E c ) from 0.5 to 4.7 kcal mol −1 . The ν b ( ν 4 ) vibrational mode denotes the bending (umbrella) motion of the CH3 D reactant (CH2 D product). Using a time-sliced, velocity-map imaging technique, we extracted the state-specific, pair-correlated integral and differential cross sections. As with other isotopically analogous ground-state reactions, an inverted vibrational population of the HF coproduct was observed. Both the step-like excitation function near the threshold and the oscillatory forward–backward peakings in the E c -evolution of the two dominant pair-correlated angular distributions at lower E c suggest a resonance-mediated, time-delay mechanism. As E c increases, the angular distribution of the HF( ν = 2) product evolves into a smooth and broad swath in the backward hemisphere, indicative of a direct rebound mechanism. One quantum excitation of the bending modes of CH3 D( ν b = 1) promotes the reaction rate by two- to three-fold up to E c = 2.1 kcal mol −1 . Broadly speaking, all major findings are qualitatively in line with previous results in the reactions of the F atom with other isotopologues. However, the rainbow feature recently observed in the CH2 D(00 ) + HF( ν = 3) product channel is entirely absent. A possible rationale is put forward, which reinforces the previous reactive rainbow conjecture and calls for future theoretical investigations.